2022
DOI: 10.1007/s00268-021-06419-3
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Trauma in Resource‐Limited Settings: A Scoping Review of Pediatric Trauma Courses

Abstract: Purpose Injury remains an important cause of death and disability globally, with 95% of all childhood injury deaths occurring in low-and lower-middle-income countries (LMICs). Pediatric trauma training, tailored to the resources in LMICs, represents an opportunity to improve such outcomes. We explored the nature of course offerings in pediatric trauma in resource-limited settings. Methods Seven databases were interrogated up to June 12, 2020, to retrieve articles examining pediatric trauma training in LMICs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In a similar assessment of paediatric inclusion in trauma education in LMICs, Pinkham et al also found an absence of internationally recognized paediatric trauma training programmes. They identified eight distinct courses (Emergency Triage, Assessment and Treatment plus Admission (ETAT+), Adapted Emergency Triage, Assessment, and Treatment (ETAT), Adapted Primary Trauma Care Course, Core Topics in Pediatric Emergency Care, Bastion Trauma Course, Pediatric Fundamental Critical Care Support, and two institutional paediatric trauma courses) [ 24 ]. All courses identified by Pinkham et al were different from those found by this review, highlighting the variability in existing educational options.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar assessment of paediatric inclusion in trauma education in LMICs, Pinkham et al also found an absence of internationally recognized paediatric trauma training programmes. They identified eight distinct courses (Emergency Triage, Assessment and Treatment plus Admission (ETAT+), Adapted Emergency Triage, Assessment, and Treatment (ETAT), Adapted Primary Trauma Care Course, Core Topics in Pediatric Emergency Care, Bastion Trauma Course, Pediatric Fundamental Critical Care Support, and two institutional paediatric trauma courses) [ 24 ]. All courses identified by Pinkham et al were different from those found by this review, highlighting the variability in existing educational options.…”
Section: Discussionmentioning
confidence: 99%
“…Pinkham et al’s [ 24 ] courses were assessed based on training modality, assessment methods, and outcomes. To assess the effectiveness of the identified courses, they used the Kirkpatrick’s Framework for Trauma Courses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational programs in trauma require hybrid educational approaches, including formal classroom techniques and simulation in immersive and realistic environments [ 1 ]. Moreover, training is required in both technical and non-technical skills [ 2 ], followed by a “hot debriefing” for knowledge and skills integration [ 1 ].…”
Section: Introductionmentioning
confidence: 99%